2010
DOI: 10.1007/s11368-010-0295-2
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum speciation in the bulk and rhizospheric soil solution of the species colonizing an abandoned copper mine in Galicia (NW Spain)

Abstract: Purpose The present study was carried out to identify and quantify the aluminum species present in the bulk and rhizospheric soil solution of the spontaneous vegetation colonizing the dump (Calluna vulgaris, Erica cinerea) and slope (C. vulgaris, E. cinerea, Salix atrocinerea) of an abandoned Cu mine in Touro (Galicia, NW Spain). Materials and methods Total dissolved aluminum was speciated into reactive Al (Alr) and acid-soluble Al (Alsa). Acid-soluble aluminum comprises colloids, polymers and/or organo-alumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Alumina surfaces have been found to be more reactive when compared with many other soil minerals, and this reactivity has been widely used for fabricating adsorbents (Al-Abadleh and Grassian 2003;Essington and Anderson 2007;Álvarez et al 2011;Wang and Shih 2011) and catalysts (Hass et al 1998;He et al 2005). Dried aluminas commonly chemisorb at least a monolayer of water when exposed to moisture at ambient conditions, and when the surfaces are hydrated, the top layer of oxide ions will be converted into a filled and square lattice of hydroxyl ions (Goldberg et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Alumina surfaces have been found to be more reactive when compared with many other soil minerals, and this reactivity has been widely used for fabricating adsorbents (Al-Abadleh and Grassian 2003;Essington and Anderson 2007;Álvarez et al 2011;Wang and Shih 2011) and catalysts (Hass et al 1998;He et al 2005). Dried aluminas commonly chemisorb at least a monolayer of water when exposed to moisture at ambient conditions, and when the surfaces are hydrated, the top layer of oxide ions will be converted into a filled and square lattice of hydroxyl ions (Goldberg et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Each sampling site was georeferenced using a portable GPS and the coordinates of each site were used for the measurement of the distance to the nearby river using geoprocessing techniques. At the laboratory, the soil adhered to the roots were removed for analysis by gently shaking and brushing the soil-rhizosphere system [37][38][39][40]. Subsequently, the samples of bulk and rhizospheric soil were air-dried, crushed, and 2-mm sieved, whereas subsamples were frozen for posterior determination of iron forms by a sequential extraction procedure.…”
Section: Soil Sampling and Field Measurementsmentioning
confidence: 99%
“…Despite the large number of studies that demonstrated the environmental problems caused by abandoned mines, just a few estimated the actual potential of waste rock piles to release metals to the surrounding ecosystems (Stromberg and Banwart, 1999;Jurjovec et al, 2002). These studies involved a detailed identification of the geochemical composition of the mine wastes, as well as their behaviour when in contact with water and soil ( Alvarez et al, 2010( Alvarez et al, , 2011Otero et al, 2012). These factors define the amount of metal that can be released by wastes and it also defines how the leachates behave in contact with natural resources, which may favour or hinder the metal bioavailability for living beings (Langman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%